ANALISIS LEGALITAS ASET KRIPTO SEBAGAI OBYEK JAMINAN DI INDONESIA - Siregar, Dahris; Wahyuni, Sri; Br Surbakti, Nindytha Elfiana; Lubis, Vasya Salsabilla; Zebua, Riyan Putra (Jurnal Yuridis, 2024)
The level of financing to meet human needs continues to increase as human needs are increasing. In this case, a guarantee agreement is drawn up to protect creditors and debtors. With the advancement of technology, to guarantee accounts receivable, can use crypto assets, are digital assets that have economic value even though they are not visible. In this study, the author uses legal and conceptual approaches. It belongs to the normative research category. Three categories of legal materials are used: primary, secondary, and tertiary. Researchers analyze and search for literature sources as a method of collecting data to collect this legal material. Within this research, legal sources are acquired through collecting, reading or recording legal sources relevant to the research problem. Studying the idea of using cryptocurrency as collateral is the aim of this project and how cryptocurrency is used as collateral in Indonesia. The study's findings revealed several things: 1) that crypto as collateral is not protected by positive law. 2) that if crypto able to serve as security, it can be used as fiduciary guarantee.